Future perspectives of genome-scale sequencing. Issue 1 (2nd January 2018) - Steyaert, Wouter; Callens, Steven; Coucke, Paul; Dermaut, Bart; Hemelsoet, Dimitri; Terryn, Wim; Poppe, Bruce
Abstract: Introduction: In recent decades, we witnessed a revolution in genetic technology. Some 20 years ago, analysing a single gene was quite laborious and time-consuming. In addition, diagnostic testing was only available for selected genes. Nowadays, whole exome analysis – a technique enabling sequencing of all protein coding sequences in the entire genome – is gradually introduced in a clinical setting. Whole genome sequencing forms the ultimate exponent of this evolution and offers an even broader application. Methods: A review of the application of these technologies in a diagnostic setting is presented. Results: Whole exome sequencing has a prominent place in modern clinical diagnostics. It offers a cost- and time-efficient way to interrogate all protein coding portions of the genome leading to a quick and adequate diagnosis, also in cases of phenotypic heterogeneity. As sequencing costs continue to drop, whole genome sequencing will take over in the near future guaranteeing a further improvement of the quality of genetic testing. Conclusion: Due to technological advances in the past decades, the field of clinical diagnostics has changed dramatically. With techniques such as whole exome and whole genome sequencing, the diagnostic yield increases serving both the patient and the health care system.